Posterior cortical atrophy in logopenic progressive aphasia: A case report - Jeevendra Kumar, Darshini; Goyal, Sheetal; Arshad, Faheem; Purushothaman, Vandana Valiyaparambath; Ramakrishnan, Subasree; Alladi, Suvarna (Frontiers in Communication, 2022)
Posterior Cortical Atrophy (PCA) and Logopenic progressive aphasia (LPA) are non-amnestic variants of Alzheimer’s disease (AD). Language deficits are a hallmark of LPA but not PCA. Studies have revealed the presence of language deficits in PCA similar to LPA, however, it has not been a consistent observation. Only alexia and agraphia are the language deficits listed in the latest consensus criteria for the classification of PCA. In this case report, we present the clinical, cognitive-linguistic, and neuroimaging features of a patient presenting with an unusual overlap of LPA-PCA. Although the diagnostic characteristics for LPA is fulfilled, the probable progression of the disease to exhibit most of the characteristics similar to PCA is highlighted. Thus it adds on to the notion of a continuum between the two atypical variants of AD. The possibility of patients with PCA exhibiting language deficits with the progression of the disease similar to that of LPA that primarily involves phonological short-term memory deficits is emphasized. The need to not undermine the language deficits irrespective of the stage of the disease in PCA is weighed upon for better identification and management via speech-language intervention programs.